2012
DOI: 10.1111/j.1744-6198.2011.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Care: Technology-Mediated Learning in Twenty-First Century Nursing Education

Abstract: Technology does not negate caring-the isolation it fosters makes transpersonal caring all the more important. We are called to create a new paradigm for nursing education that merges Nightingale's vision with technology's promise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Despite correlating evidence of positive experiences with simulations using standardized patients in nursing and medical education [40,41], a review of Internet-based simulations showed that video based scenarios have been used less than virtual simulations and that professional actors have most often been used to play patients in previous video based scenarios [16]. Simulated scenarios are also perceived to lack nurse caring aspects [42] because they often focus on teaching acute nursing care [43][44][45]. On the contrary, the participants in our study perceived that the video based SG managed to demonstrate the caring relationship between the RN and her patient and contributed to immersion.…”
Section: Participants' Perception Of the Sgmentioning
confidence: 96%
“…Despite correlating evidence of positive experiences with simulations using standardized patients in nursing and medical education [40,41], a review of Internet-based simulations showed that video based scenarios have been used less than virtual simulations and that professional actors have most often been used to play patients in previous video based scenarios [16]. Simulated scenarios are also perceived to lack nurse caring aspects [42] because they often focus on teaching acute nursing care [43][44][45]. On the contrary, the participants in our study perceived that the video based SG managed to demonstrate the caring relationship between the RN and her patient and contributed to immersion.…”
Section: Participants' Perception Of the Sgmentioning
confidence: 96%
“…In this study, the researchers did validate the simulation scenarios by clinical experts within the field of hemodialysis. Although there seems little written on strengthening nurses' caring attitudes and behaviours through simulation activities, Diener and Hobbs (2012) pointed out the added value of using simulation with nursing students to learn Watson's transpersonal caring relationship. Consequently, and following the arguments presented above, the addition of a simulated clinical situation with a standardized patient (comedian), that would afford participants the chance to exercise their know-how related to the caring approach, seems most appropriate.…”
Section: Discussion Intervention Feasibilitymentioning
confidence: 99%
“…In order to make up for the shortage, Simulated Patients (SPs) are used for the education in some medical universities [5].…”
Section: Introductionmentioning
confidence: 99%